2020
DOI: 10.1002/mrd.23353
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling, actin polymerization, and follicle activation in fragmented human ovarian cortex

Abstract: The Hippo pathway has been associated with regulation of early follicle growth. Studies of murine ovaries suggest that changes in the actin cytoskeleton, caused by fragmentation, result in inhibition of the Hippo pathway, and in turn, may activate follicle growth. In humans, the connections between fragmentation, the actin cytoskeleton, and follicle activation are yet to be confirmed. In this study, we investigated the impact in vitro fragmentation of a human ovarian cortex on (a) actin polymerization, (b) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Tissue preparation for cryopreservation includes the removal of the medulla by scraping with a scalpel to prepare the cortical tissue to the required thickness of 1 mm. This most probably results physical removal of secondary and early pre-antral follicles, mostly situated on the dissection plane as previously demonstrated ( De Roo et al , 2017 ; Herraiz et al , 2020 ; Lunding et al , 2020 ), but also in an unintended activation and burnout of residing follicles of all maturation stages in the cortex fragments. If so, ovarian tissue preparation for cryopreservation might benefit by keeping the medulla (partially) intact.…”
Section: Discussionmentioning
confidence: 53%
“…Tissue preparation for cryopreservation includes the removal of the medulla by scraping with a scalpel to prepare the cortical tissue to the required thickness of 1 mm. This most probably results physical removal of secondary and early pre-antral follicles, mostly situated on the dissection plane as previously demonstrated ( De Roo et al , 2017 ; Herraiz et al , 2020 ; Lunding et al , 2020 ), but also in an unintended activation and burnout of residing follicles of all maturation stages in the cortex fragments. If so, ovarian tissue preparation for cryopreservation might benefit by keeping the medulla (partially) intact.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, a study conducted on human ovaries could not prove the relevance of drug-free IVA technique, since it did not find a relationship between the fragmentation of the ovarian tissue and actin polymerization, nor between the fragmentation and the effectors of the Hippo pathway; also it did not show an increase in the number of growing follicles from the fragmented tissue ( Lunding et al , 2020 ). However, this trial was limited to nine women and does not rule out a transient effect on this pathway what is difficult to assay, as demonstrated by other authors ( Grosbois and Demeestere, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it decreased with the extension of culture time (P< 0.05), indicating that the Hippo signaling pathway regulates the proliferation of cancer cells by acting on target genes. Another study suggested that CCN1 has the effect of promoting YAP-TEAD expression activity, which is opposite to the effect of CCN2 (36,37).To prove the inhibitory effects of non-coding RNA LINC00857 on cell proliferation, the cell apoptosis rate of the response group and the control group was determined byCCK8. It was found that After 12, 24, 36, and 48 hours, the apoptosis rates of the response group were higher versus the control group, and the difference was notable (P<0.01).…”
Section: The Effect Of Down-regulated Yap-tead Expression On Cell Pro...mentioning
confidence: 99%